ANDIN-MU: Development of Android-Based Descriptive Text Interactive Multimedia Materials in High School English Subjects - Ahmed, Mohammed Alameen; Kumalasari, Nur (Assyfa Learning Journal, 2023)
In learning there is a process of changing the behavior of a person who is initially unaware of something then becomes aware. In other words, there is a process of conveying knowledge between teachers and students or using learning materials. The purpose of this study was to develop interactive multimedia based on Android descriptive text material for Class X SMA Pasuruan English. This study uses the ADDIE model. In this development model there are five steps in the process, but in this study the researchers modified some of the steps used and adapted them to the environmental conditions affected by the Covid-19 pandemic climate. The steps taken are 4 out of 5 steps, namely (1) analysis (2) design (3) development and (4) evaluation. Collecting data in this study through interviews, documentation and questionnaires. The results showed that the media validation results scored 80%, while the content validation results obtained a score of 78%. The Likert scale used in the data calculation process shows that the developed interactive multimedia is very feasible to use in Pasuruan High School